FSI Modeling Approach to Develop Right Ventricle Pulmonary Valve Replacement Surgical Procedures with a Contracting Actuator and Improve Ventricle Ejection Fraction. (2015) - Yang, Chun; Tang, Dalin; Vasilyev, Nikolay; Rathod, Rahul; Geva, Tal; del Nido, Pedro J.
Abstract: Image-based computational modeling has been used more and more for cardiovascular disease management and surgical planning in recent years. Computational modeling could perform virtual surgery with different surgical options avoiding risks associated with actual surgical experimentation on patients. For patients with repaired tetralogy of Fallot (TOF) needing right ventricle (RV) pulmonary valve replacement (PVR), the current surgical approach, which includes pulmonary valve replacement/ insertion, has yielded mixed results. In this paper, we propose a new surgical option placing a contracting actuator in the right ventricle to improve RV function measured by ejection fraction (EF). An interdisciplinary approach is proposed to combine cardiac magnetic resonance (CMR) imaging, modeling, and mechanical engineering techniques to construct the mechanical actuator, build the ventricle models, perform virtual surgery, demonstrate feasibility of the new surgical procedure with actuator insertion, and identify optimal mechanical conditions under which optimal surgical outcome could be achieved.